Strategi Perilaku Ibu Dalam Pencegahan Penyakit Diare Pada Balita Di Kelurahan Bandar Kidul Kota Kediri: Mother’s Behavioral Strategies in Preventing Diarrhea in Toddlers at Bandar Kidul Kediri - Vivien PURNAMASARI, S.KM., M.Kes.; Akhmadi Abbas; Tutut Pujianto; Anastasya Putri Wisnu Indrasawati; Marianti Dwi Safitri; Ratna Anneha Rahmaniya An Nur; Reva Aurelia Putri; Umi Hanip; Eliza Nur Rosidah (Fakultas Teknologi dan Manajemen Kesehatan, 2026)
Diarrhea in toddlers remains a public health problem in Kediri City. Data from the Kediri City Health Office in 2024 showed 3,755 cases of diarrhea, with the Campurejo Community Health Center (Puskesmas) as the highest contributor, with 257 cases among toddlers in Bandar Kidul Village. This study aims to determine maternal behavioral strategies for preventing diarrhea in toddlers in Bandar Kidul Village, Kediri City. This study used a qualitative method with a descriptive approach. Nine informants participated: 7 mothers of toddlers as primary informants and 2 key informants: health cadres and the person in charge of the Campurejo Community Health Center diarrhea program. Data were collected through in-depth interviews and analyzed thematically. The results indicate that mothers of toddlers have adequate knowledge and attitudes, but diarrhea prevention practices are not consistently implemented. The study's conclusions highlight the need for continuous strengthening of health promotion to improve diarrhea prevention behaviors in toddlers.